Eksposur materi autentik di kelas Bahasa Inggris sebagai Bahasa Asing - Zaitun Qamariah (Pusat Riset dan Inovasi Nasional, 2023)
Grammar rule-based learning is frequently emphasized in traditional English classes in Indonesian primary, middle, and high schools. The test-based education system creates classes that produce a type of English that does not appear to be spoken outside of the classroom. As a result, the students struggle to adjust to English by native speakers in the real world. Those who connect with native speakers must constantly alter their linguistic behavior in areas of language where suitable instruction was not provided. To address this phenomenon, it is important to build a self-created